2019
DOI: 10.1039/c8sc03759k
|View full text |Cite
|
Sign up to set email alerts
|

Structural insights reveal a recognition feature for tailoring hydrocarbon stapled-peptides against the eukaryotic translation initiation factor 4E protein

Abstract: We have revealed a non-canonical recognition feature that can modulate the binding kinetics of hydrocarbon stapled-peptides interactions with the eIF4E protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 44 publications
(52 reference statements)
0
25
0
Order By: Relevance
“…The stapled peptide strategy has been successfully applied to inhibit several PPIs of therapeutic potential including, BCL-2/Mcl-1 family, 21 24 β-catenin–TCF, 25 Rab–GTPase-effector, 26 ERα–coactivator protein, 27 Cullin3–BTB, 28 VDR–coactivator protein, 29 eIf4E 30 and p53–Mdm2/Mdm4. 31 34 Noteworthy, in the case of p53–Mdm2/Mdm4, a dual selective stapled peptide (ALRN-6924) has been further successfully advanced to phase II clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…The stapled peptide strategy has been successfully applied to inhibit several PPIs of therapeutic potential including, BCL-2/Mcl-1 family, 21 24 β-catenin–TCF, 25 Rab–GTPase-effector, 26 ERα–coactivator protein, 27 Cullin3–BTB, 28 VDR–coactivator protein, 29 eIf4E 30 and p53–Mdm2/Mdm4. 31 34 Noteworthy, in the case of p53–Mdm2/Mdm4, a dual selective stapled peptide (ALRN-6924) has been further successfully advanced to phase II clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…Peptidomimetics guarantee enhanced protection against peptidases, improved systemic delivery and cell penetration, high target specificity and poor immune response and they are already in use against different pathologies, such as cancer and diabetes (Vagner et al, 2008;Zhang et al, 2018). In this context, computational approaches such as MetaD (Figure 2A) and classical MD simulations ( Figure 2B) demonstrated to be valid tools to drive the conversion of peptides in more active peptoids/peptidomimetics, targeting αvβ6 RGD-integrin in one case (Di Leva et al, 2018) and the eukaryotic translation initiation factor 4E (eIF4E) in the other (Lama et al, 2013(Lama et al, , 2019.…”
Section: Discussionmentioning
confidence: 99%
“…Rational design subsequently led to stapled-peptides with enhanced target residence time targeting an unexploited patch on the surface of eIF4E. 43 Similar observations were made by Gallagher et al 44 Initially, the group measured the helical propensities of the linear wild-type 4E-BP1 and eIF4G peptides and found that the 4E-BP1 sequence exhibits greater helicity in solution than the eIF4G. SPR was used to profile the temperature- and salt-dependence of the peptide–protein interactions; whilst eIF4G binding was found to depend on electrostatic contributions and vary in binding kinetics with temperature, 4E-BP1 was relatively unaffected.…”
Section: Enhancing Protein Binding Affinitymentioning
confidence: 99%